S2-1. Pathophysiology of involuntary movement based on DBS surgery. Issue 5 (May 2018) - Kobayashi, Kazutaka; Watanabe, Mitsuru; Oshima, Hideki; Fukaya, Chikashi; Yoshino, Atsuo
Abstract : A model that explains the pathophysiological condition of involuntary movements as the degree of output levels of the basal ganglia has been proposed. Because high frequency deep brain stimulation (DBS) has an effect similar to ablation, an initial hypothesis regarding the mechanism of DBS was the inhibition of excessive activity at the target site. A recent theory states that an abnormal neural activity pattern such as oscillation in the basal ganglia disrupts motor control. Local field potential recordings for Parkinson disease (PD) have shown increased beta-band oscillations associated with motor symptoms of PD. High-frequency stimulation of the subthalamic nucleus suppresses beta-band oscillations. Meanwhile, at the target site, high-frequency DBS has inhibitory effects on the soma and excitation effects on the axon, thereby influencing the target site and the neural activity of the projection site. DBS possibly acts by modifying or obstructing an abnormal nerve activity pattern in the neural network by combining different effects on the soma and axons, rather than by just suppressing the target site.